Computed tomography angiography is associated with low added utility for detecting clinically relevant vascular injuries among patients with extremity trauma - Deborah M Stein; Riley Brian; Daniel J Bennett; Woon Cho Kim (Trauma Surgery & Acute Care Open, 2021)
Background Extremity CT angiography (CTA) is frequently used to assess for vascular injury among patients with extremity trauma. The injured extremity index (IEI), defined as the ratio of systolic occlusion pressure between injured and uninjured extremities, has been implemented to screen patients being considered for CTA. Physical examination together with IEI is extremely sensitive for significant extremity vascular injury. Unfortunately, IEI cannot always be calculated. This study aimed to determine whether patients with normal pulse examinations and no hard signs of vascular injury benefitted from further imaging with CTA. We hypothesized that CTA has become overused among patients with extremity trauma, as determined by the outcome of vascular abnormalities that underwent vascular intervention but were missed by physical examination.Methods The charts of traumatically injured patients who underwent extremity CTA were retrospectively reviewed. This study was performed at a level 1 trauma center for patients who presented as trauma activations from September 1, 2019 to September 1, 2020.Results One hundred and thirty-six patients with 167 injured limbs were included. Eight limbs (4.8%) underwent an open vascular operation, whereas five limbs (3.0%) underwent an endovascular procedure. One of the 167 limbs (0.6%) had a vascular injury seen on CTA and underwent intervention that was not associated with a pulse abnormality or hard signs of vascular injury. This patient presented in a delayed fashion after an initially normal IEI and examination. Proximity injuries and fractures alone were not highly associated with vascular injuries.Discussion Many patients with normal pulse examination and no hard signs of vascular injury underwent CTA; the vast majority of these patients did not then have a vascular intervention. Given the consequences of missed vascular injuries, further work is required to prospectively assess the utility of CTA among patients with extremity trauma.Level of evidence III.